Personal management - U K Singh; Dewan, J M (New Delhi : A. P. H., 1996)
Outlines the requirements for earning the Boys Scouts merit badge in personal management, with information on managing money, being a smart shopper, using bank accounts, borrowing money, and saving for the future.
Bibliographic material included.
Keywords: Finance, Personal